2011
DOI: 10.1021/nl202303y
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Nanowire-Based CMOS-Compatible Field-Effect Transistor Nanosensors for Ultrasensitive Electrical Detection of Nucleic Acids

Abstract: We herein report the design of a novel semiconducting silicon nanowire field-effect transistor (SiNW-FET) biosensor array for ultrasensitive label-free and real-time detection of nucleic acids. Highly responsive SiNWs with narrow sizes and high surface-to-volume-ratios were "top-down" fabricated with a complementary metal oxide semiconductor compatible anisotropic self-stop etching technique. When SiNWs were covalently modified with DNA probes, the nanosensor showed highly sensitive concentration-dependent con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
205
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(218 citation statements)
references
References 43 publications
4
205
0
6
Order By: Relevance
“…(11) The back-gate-controlled field effect on device sensitivity was studied using a pH sensing experiment by our group. (10) Figure 3(a) shows as-prepared SiNW devices characterized as nanoscale pH sensors. The real-time current of the silicon nanowire decreased stepwise with a discrete change in pH from 5.0 to 9.0 [ Fig.…”
Section: Ion Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…(11) The back-gate-controlled field effect on device sensitivity was studied using a pH sensing experiment by our group. (10) Figure 3(a) shows as-prepared SiNW devices characterized as nanoscale pH sensors. The real-time current of the silicon nanowire decreased stepwise with a discrete change in pH from 5.0 to 9.0 [ Fig.…”
Section: Ion Detectionmentioning
confidence: 99%
“…In general, there are two major techniques for fabricating SiNWs: top-down (10) and bottomup. (11) SiNWs prepared by the bottom-up approach are normally catalytically synthesized by chemical vapor deposition (CVD).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Gao et al (2011) reported a highly responsive FET sensor array for the ultrasensitive and real-time detection of DNA. A CMOS-compatible top-down anisotropic self-stop etching technology was used to fabricate a narrow-size nanowire with high surface-to-volume ratios ( Figure 8A).…”
Section: Dna-dna/rna Hybridizationsmentioning
confidence: 99%
“…In addition, SiNW-FETs can perform rapid, ultrasensitive, and multiplexed detection of the desired targets independent of any labels (Patolsky et al 2006a, Gao et al 2007). In the past decade, this nanobiosensor has been widely used to detect a variety of molecule binding events with sensitivities below picomolar concentrations (Gao et al 2011(Gao et al , 2012(Gao et al , 2013. Because of the broad implementation of SiNW biosensor in molecule-molecule interactions and an extendable application in real-time in vivo monitoring (Tian et al 2010, Duan et al 2012a, Qing et al 2014, we summarize the recent advances in SiNWFETs with emphasis on a variety of molecule interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Having dimensions on the same scale like the target molecules and a high surface-to-volume ratio, their electrical response is expected to exceed that of more conventional thin-film devices for real-time monitoring of complex environments. [4][5][6][7][8] A plethora of studies addressed their performance as ultra-sensitive detectors for gas, [9][10][11] pH, 1,12,13 nucleic acids, 14 and proteins. 1,12,15 For biosensing, SiNWs were developed for use mainly in aqueous media, in situ 16 -akin to implantable devices, or ex situ 1,12,13 via microfluidic approaches.…”
mentioning
confidence: 99%